Inovasi Strategi Pembelajaran Inkuiri dalam Pembelajaran - Risqyanto Hasan Hamdani; Syaiful Islam (LP2M STIT Palapa Nusantara, 2019)
This research is motivated by assumption that in maximizing student learning result it is deemed necessary to present new inovation in a learning process. This study was purposed to fully describe the role of inquiry learning strategies that have collaborated with other learning strategies or methods in maximizing learning result obtained by students of SMKN 02 KRAKSAAN. The implementation of strategies or learning methods is considered to be dominantly influential in improving student learning result. This research method uses descriptive research methods that are collaborative in qualitative form. The subject of this research are the teachers and students of SMKN 02 KRAKSAAN. Research data obtained from interviews, observations, and documentation. The result of this study showed an increase in the average student learning result by 15 points (documentation result) from the previous action (the implementation of inquiry learning strategies). Things that show the enormity of the influence given by inquiry learning strategies in maximizing student learning result.